Identification of Artemis and PARP-1 interacting factors: A yeast two hybrid screening approach - Farzadfar, Rahin (University of Ottawa (Canada), 2009)
The genomic integrity of the cell is under the constant threat of DNA damage from endogenous and exogenous sources. In response to DNA damage mammalian cells elicit a highly complex, yet coordinated series of cellular responses, which are triggered by the detection of DNA lesions and ultimately lead to cell survival (DNA repair) or apoptosis. Artemis and PARP-1 are two proteins with significant implications in the various branches within the DNA damage response network. A series of yeast two hybrid screening (Y2H) experiments were conducted using both classical and interacting mating Y2H systems to find Artemis and PARP-1 interacting factors. The ATRX protein was identified as a putative interactor of Artemis, Caspase-7 and an "unkown" protein were identified as putative interactors of PARP-1 binding factors. In addition a rare case of false positives were identified and characterized. Furthermore, the strengths and limits of each Y2H system, as well as troubleshooting techniques developed to increase the efficiency of each system were thoroughly examined.
Keywords: Chemistry, Biochemistry.